2016
DOI: 10.1080/02643294.2016.1188798
|View full text |Cite
|
Sign up to set email alerts
|

The neural network for tool-related cognition: An activation likelihood estimation meta-analysis of 70 neuroimaging contrasts

Abstract: The ability to recognize and use a variety of tools is an intriguing human cognitive function. Multiple neuroimaging studies have investigated neural activations with various types of tool-related tasks. In the present paper, we reviewed tool-related neural activations reported in 70 contrasts from 56 neuroimaging studies and performed a series of activation likelihood estimation (ALE) meta-analyses to identify tool-related cortical circuits dedicated either to general tool knowledge or to task-specific proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 118 publications
2
70
0
Order By: Relevance
“…On classic two-route accounts of visual processing, reach and grasp actions mediated by the bilateral dorsal visual stream operate on currently-viewed structural characteristics of objects, and are largely inaccessible to consciousness (Goodale and Milner, 1992, 2013; Milner and Goodale, 1995; Jeannerod et al, 1995b). More recent evidence indicates, however, that skilled use actions are mediated by relatively more ventral regions (the “ventro-dorsal stream”), are strongly left-lateralized, and are consciously accessible (e.g., Ishibashi et al, 2016; M. Martin et al, 2016; Tobia and Madan, 2017; see Binkofski and Buxbaum, 2013; for discussion).…”
Section: Discussionmentioning
confidence: 99%
“…On classic two-route accounts of visual processing, reach and grasp actions mediated by the bilateral dorsal visual stream operate on currently-viewed structural characteristics of objects, and are largely inaccessible to consciousness (Goodale and Milner, 1992, 2013; Milner and Goodale, 1995; Jeannerod et al, 1995b). More recent evidence indicates, however, that skilled use actions are mediated by relatively more ventral regions (the “ventro-dorsal stream”), are strongly left-lateralized, and are consciously accessible (e.g., Ishibashi et al, 2016; M. Martin et al, 2016; Tobia and Madan, 2017; see Binkofski and Buxbaum, 2013; for discussion).…”
Section: Discussionmentioning
confidence: 99%
“…While our main analyses focus on putative spokes within visual and motor cortex, the literature on tool semantics suggests two additional sites that could also make a greater contribution to the identification of manipulable manmade objects than animals. First, left premotor cortex is associated with tool and action comprehension [22, 23, 29, 78], although this site is also likely to be influenced by the control demands of semantic tasks [79, 80]. We present results for this site in S2 Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We present results for this site in S2 Fig. Second, left inferior parietal cortex is associated with tool use and hand praxis [22, 78]. We do not present a POI analysis for this location because there was no clear response to the task within this region in the whole-brain beamforming results (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Decoding hand-object sounds in primary somatosensory cortex In addition, much research concerning the neural processing of tools has reported strong left lateralization of the tool network in right-handed participants (as our participants were; Ishibashi, Pobric, Saito, & Lambon Ralph, 2016;Lewis, Brefczynski, Phinney, Janik, & DeYoe, 2005;Lewis, Phinney, Brefczynski-Lewis, & DeYoe, 2006) although this would suggest left-lateralization for both sounds and images/videos. However it may be the case that such left lateralization depends upon object directed action content being present (or strongly implied), as was the case in the current study.…”
Section: Hemispheric Differences In Auditory and Visually Triggered Cmentioning
confidence: 56%